iPark: automated smart parking system - Rahman Atiqur (International Journal of Advances in Applied Sciences, 2021)
Parking problems became ubiquitous and are growing at an alarming rate in every major city. It causes parking problems which cause traffic jams, driver frustration, and pollution. Time we visit different public places for example shopping centers, multiplex movies hall and lodging houses during carnivals or holidays, it makes the added parking difficult. Checking out a parking lot results in 40% to 50% of traffic jams. Due to this, car parking, in turn, causes the traffic issue. There are some problems associated with car parking like the way to control the amount of cars within the parking zone, monitoring the movement of the car in/outside of the parking zone, checking whether there's an area inside for more cars or not, and therefore the safety to park. This paper proposes an answer to these problems using the concept of the web of Things. iPark is a fully automated system that senses the entry and exit of a car, displays the entire number of cars parked within the parking zone on screen, and the way many free spaces are available within the parking lot.